Effectiveness of Cognitive Exercise on Anxiety Levels in the Elderly - Hendrawati Hendrawati; Muhammad Arifki; Riyanah Riyanah (GLOBAL HEALTH SCIENCE GROUP, 2026)
Anxiety is a common psychological problem experienced by older adults and can impact quality of life and cognitive function. Various non-pharmacological interventions have been used to reduce anxiety in older adults, but most studies still focus on physical activity and relaxation. Empirical evidence regarding the effectiveness of cognitive training on anxiety in older adults is limited and shows varying results. Therefore, this study was conducted to assess the effectiveness of cognitive training in reducing anxiety levels in older adults. Objective to determine the effectiveness of cognitive gymnastics on anxiety levels in the elderly at the Tresna Werdha 3 Social Home. This study used a quantitative approach with a pre-test and post-test design in one group. A sample of 45 elderly individuals was selected using the Slovin formula. Data collection was conducted through interviews and the Hamilton Anxiety Rating Scale (HARS) questionnaire. The HARS questionnaire was valid (0.30 – 0.80) and reliable (Cronbach’s Alpha 0.93). Data analysis was performed using univariate and bivariate methods using paired sample t-tests. Before the intervention, most elderly individuals experienced mild (46.8%) to moderate (31.9%) anxiety. After the intervention, the proportion of elderly with mild anxiety increased to 60%, and 8.9% experienced no anxiety. Paired Sample t-test results showed a significant decrease in anxiety scores (p < 0.001). Cognitive gymnastics is effective in significantly reducing anxiety levels in elderly individuals and can be used as a non-pharmacological intervention to improve the psychological well-being of elderly individuals.